Related Parenting Patterns with Smartphone Use in Children Aged 4-5 Years - Hasanah, Yulia Rachmawati; Widhiyanto, Alwin (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2023)
The parenting styles commonly applied include protective, demanding, dominant, indulgent, permissive, rejective, critic, and inconsistent. There are no activities outside the home, including learning activities at school. It is unavoidable, that the consequences of parenting greatly affect the growth and development of children. On the other hand, smartphones are already very attached and become a necessity in society in the current pandemic era. Without realizing it, smartphones have impacts on the next generation of the nation. There is a positive impact of smartphones on children's development, but there is a negative impact on children who are addicted to smartphone use. Based on a preliminary study conducted at Zainul Hasan Genggong Kindergarten in children aged 4-5 years out of 10 children familiar with smartphones, 2 children (20%) of them use smartphones belonging to their parents, and 8 children (80%) play their own smartphones that have been installed on their own. facilitated by their parents. Of the 10 children when they use a smartphone, 6 of them are limited in their use time but are not accompanied when using a smartphone, and 4 children (40%) are not restricted by their parents and are not accompanied when using a smartphone. The research design that will be used in this research is Cross Sectional. The population of this study were all parents who have children aged 4-5 years in Zainul Hasan Genggong Kindergarten, using purposive sampling technique, with a population of 60 mothers, with a sample of 40 mothers. Collecting data using questionnaires and analyzed by chisquer statistical test. The results obtained are a strong relationship between parenting patterns and the use of smartphones in children aged 4-5 years with a spearman correlation value of 0.045 <0.05.